KEANEKARAGAMAN JENIS VEGETASI PENYUSUN HUTAN SEKUNDER DESA TANJUNG BUNUT KECAMATAN TAYAN HILIR KABUPATEN SANGGGAU - Mirdat, Jamal; Anwari, Sofwan; Ardian, Hafiz (Universitas Tanjungpura, 2017)
Secondary forest is part of the tropical rain forest in West Kalimantan which has a fairly high biodiversity. Benefits to be derived from secondary forests include wood as building materials and firewood, rattan as the raw material crafts, vegetables, fruits and pharmaceuticals. A number of benefits that are owned by secondary forests, making this region can not be separated from the influence of human activity and hand mix, especially people around who generally take the benefits and results of the forest area. 2.2 ha total area of research. The method used is the method with path-shaped combination of lines and line terraced placed purposive sampling, Based on the results of research conducted on the Secondary Forest Tanjung Bunut District of Tayan Hilir Sangggau found 24 type vegetation ranging from seedlings, saplings, poles, and tree. Based on their research results visible to differences in the number of species and individuals who found. Number of species and individuals were found in five of these pathways, namely the seedling stage 96 species, with the number of 894 individuals, saplings 63 species, with the number of 725 people, found 57 species of small trees , the number of 595 people, and there are 51 kinds of tree with the number of individuals 441. the structure of secondary forest vegetation Tanjung Bunut still good because forest cover consisting of a wide variety of plant species with equitable conditions. Keywords: Dominant species, important value index, Secondary forest, Species biodiversity, Tanjung Bunut village.